What drives user stickiness in digital currency? The moderating role of contextual complexity - Xu, Yang; Lee, Eunmi Tatum (International Journal of Innovative Research and Scientific Studies, 2025)
The understanding of the factors that drive user stickiness in extant studies remains limited to date. To bridge the research gaps, this study explored whether system quality, information quality, and service quality influence user stickiness in digital currency, based on the IS Success Model. We further investigated the moderating role of contextual complexity by drawing upon complexity theory. By surveying 528 Chinese users of the electronic Chinese Yuan, our hierarchical regression analysis revealed that system quality, information quality, and service quality are positively associated with user stickiness in digital currency. We also found that high contextual complexity positively moderates these relationships. Our findings suggest that improving system quality, information quality, and service quality are crucial factors for increasing user stickiness in digital currency. Our findings also suggest that greater contextual complexity enhances user-system interactions and facilitates the co-evolution of digital currency usage environments. Our study provides practical contributions for policymakers and managers by highlighting that harmony, derived from the transparency of digital currency, an innovative institutional environment, and an efficient system, enables innovation and enhances the retention of digital currency.